1999
DOI: 10.1159/000018064
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Topical Antioxidants on UV-Induced Erythema Formation when Administered after Exposure

Abstract: Background: Photoprotective effects of topically applied antioxidants when applied before ultraviolet radiation (UVR) exposure are well known. Their protective effect when applied after UVR exposure is, however, less established. Objective: In a randomized, double-blinded, placebo-controlled human study the short-term photoprotective effects of different antioxidants and of their combinations were evaluated when applied after UVR exposure. Methods: Melatonin (N-acetyl-5-methoxytryptamine), vitamin E (α-tocophe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 21 publications
3
52
0
2
Order By: Relevance
“…Skin damage is a rapid event, and vitamin C prevents such damage only when present in relevant concentrations during oxidative stress [35]. Impaired AA recycling can result in a rapid vitamin C depletion and decreased antioxidant defence.…”
Section: Discussionmentioning
confidence: 99%
“…Skin damage is a rapid event, and vitamin C prevents such damage only when present in relevant concentrations during oxidative stress [35]. Impaired AA recycling can result in a rapid vitamin C depletion and decreased antioxidant defence.…”
Section: Discussionmentioning
confidence: 99%
“…5 and 63 ). Clinical studies indicated that melatonin is able to prevent sun damage only when it is administered before UVR and it is present in relevant concentrations directly at the irradiation site ( [64][65][66][67] ). These observation have strong experimental support from in vitro studies.…”
Section: Melatonin As Protector Against Skin Damagementioning
confidence: 99%
“…This had not been observed during USPF and RF testing, despite it being evidenced in previous research. It could be demonstrated that topically applied antioxidants exhibit protective effects during UV irradiation [21,22], whereas previously, diets rich in antioxidants had been shown to reduce erythema formation [23]. As cream 1 was not tested, no conclusions regarding the protective effects of antioxidants independent of the presence of chemical filters could be drawn in this study.…”
Section: Resultsmentioning
confidence: 83%